Multi-interval linear ordinary boundary value problems and complex symplectic algebra - Everitt, W. N. (William Norrie), 1924-2011 (Memoirs of the American Mathematical Society ;, 2001)
Introduction: Goals, organization Some definitions for multi-interval systems Complex symplectic spaces Single interval quasi-differential systems Multi-interval quasi-differential systems Boundary symplectic spaces for multi-interval systems Finite multi-interval systems Examples of complete Lagrangians Bibliography.